Docking Analysis Of Phenethyl Isothiocyanate (Peitc) From Nasturtium Officinale (Watercress), On 4 - (Methylnitrosamino) -1- (3 - Pyridyl) - 1- Butanone(Nnk), Carcinogenic Action In Oral Cancer - PA.RAJALAKSHMI,; S.AGALYAA, (International Journal of Pharma and Bio Sciences, 2010)
NNK (4-(methyl-nitrosamino)-1-(3-pyridyl)-1-butanone), a nitrosamino compound present in tobacco cause cancer in oral cavity. NNK a potent procarcinogen, when metabolically activated by Cytochrome P450, the NNK procarcinogen was converted into NNK carcinogen .The Cytochrome P450 and NNK complex cause oral cancer. Watercress, (Nasturtium officinale) a green leafy cruciferous vegetable used in salads, sandwiches and as an herb. The chemo preventive agent Phenethyl Isothiocyanate (PEITC) present in Watercress (Nasturtium officinale) acts as an inhibitor of the metabolism of NNK with Cytochrome P450. Docking analysis was done to predict the binding affinity of PEITC to Cytochrome P450, which inhibits the binding action of NNK to Cytochrome P450 to prevent oral cancer.